DIBR – Fuzzy MARCOS model for selecting a location for a heavy mechanized bridge - Tešić, Duško Z.; Božanić, Darko I.; Pamučar, Dragan S.; Din, Jamalud (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: The paper presents the DIBR-FMARCOS model of multi-criteria decision-making  for defining a location for placing a bridge over an obstacle using a heavy mechanized bridge (TMM-3). After the application of the proposed model, the sensitivity analysis of the output results was performed and it was concluded that the model is stable, i.e. that the model gives consistent results and that its application is possible in real situations.Methods: The DIBR method was used to determine the weight  coefficients of the criteria, while the ranking of alternatives was performed by the FuzzyMARCOS method.Results: The application of this model has led to the selection of the location for placing a bridge from the TMM-3 set, based on the defined criteria. After applying the proposed model, the sensitivity analysis of the output results was performed and the consistency of the output results of the method was proven.Conclusion: Finally, it was concluded that the proposed model can be applied in practice, because it gives stable output results. It was also concluded that the DIBR method facilitates the process of obtaining the weight coefficients of the criteria, and the FMARCOS method copes well with unclear and inaccurate input data and has good stability. This model can be further improved by more detailed operationalization of the criteria, as well as by the use of other different methods for determining the weights of the criteria and ranking.
Keywords: location; bridge; MCDM; DIBR; Fuzzy; MARCOS